RANCANGAN GEOMETRI PELEDAKAN BATUAN GRANODIORIT PT. GILGAL BATU ALAM LESTARI MEMPAWAH KALIMANTAN BARAT - Murad Murad (Sekolah Tinggi Teknologi Industri Padang, 2022)
PT. Gilgal Batu Alam Lestari (PT. GILBAL) is a granodiorite mining company whose activities include stripping overburden, excavation/mining using the blasting method, transporting blasted materials and processing granodiorite in processing units. The blasting design parameters are influenced by the proper selection of the hole diameter and pitch height. The effect of burden, spacing, stemming, subdrilling, the depth of the shot holes is very important to anticipate the geological conditions and the type of explosives used. The purpose of this research is to study and calculate the size of rock fragmentation resulting from blasting and analyze the size distribution of fragmentation in blasting activities using the Kuz-Ram method and Split Desktop 4.0 software. The method of solving the problem in this research is to design a good blasting geometry to get the granodiotite fragmentation size < 50 cm. The proposed geometric design uses RL. Ash, CJ. Konya and ICI-Explosive. The results of the design RL. Ash obtained burden (B) 1.95 m, spacing (S) 2.34 m, steaming (T) 1.36 m, subdrilling (J) 0.585 m, blast hole depth (H) 5.85 m, ladder height ( L) 6 m, Powder column (PC) 4.49 m, hole diameter (De) 3 inches. CJ. Konya obtained B 2 m, S 2.375 m, T 1.4 m, J 0.6 m, H 5.69 m, L 6 m, PC 4.29 m, De 3 inches. According to the ICI-Explosive theory, B 1.9 m, S 1.9 m, T 1.52 m, J 0.608 m, H 6.08 m, L 6 m, PC 3.952 m, De 3 inches. The proposed design using ICI-Explosive and Kuz-ram found that the fragmentation size of 50 cm passed the 89.10% sieve and the cost of blasting was Rp. 115,237,500,-more likely to be implemented because it requires minimal blasting costs and fragmentation in accordance with the bucket capacity and company design compared to the RL. Ash method. and CJ. Konya. The distribution of fragmentation using Split Desktop obtained a fragmentation size of 50 cm which passed the sieve of 97.11%. It is necessary to conduct a more in-depth study related to the ideal blasting geometry from a technical and economic point of view as well as strict supervision of the blasting geometry design that has been designed to be implemented in the field.